The Impact of Self-Directed Learning on Students' English Reading Comprehension Ability (Proceedings of English Linguistics and Literature, 2022)
Self-directed learning (SDL) refers to practice in the classroom for individual students' English reading comprehension skills over the course of two meetings in this study. The objective of this study is to determine the impact of SDL on English reading comprehension ability and its size, as well as how SDL enhances English reading comprehension ability of 30 students from one of Jakarta's education institutions. An embedded mixed methods design with an embedded experimental model version is used in this work. Common European Framework of Reference for Languages (CEFR) part gave quantitative data, and the Learning Summary and Evaluation Sheets, as well as instructor reflection, yielded qualitative data. The dependent samples t-test reveals that, on average, the English reading comprehension ability of the subject students before the SDL (M = 12.30, SD = 2.76), and that after the SDL project (M = 13.33, SD = 3.30) is significantly different (p = 0.01). This means that, on average, the English reading comprehension ability of the students in the post-test significantly increases from the pretest. The effect size is 0.34, which means that its magnitude is “medium”. SDL improves reading ability in terms of “increasing awareness of reading strategy use” (53%), “developing learning responsibility and effort” (20%), “providing freedom to learn” (20%), and “building self-confidence to read” (7%). Implications and applications are discussed, and recommendations are provided.